The Effect of Environmental Information Disclosure on Cash Flow Volatility with the Moderating Role of Firm Size and Ownership Structure - Mazidabadi, Effat; Khosravipour, Negar; Bidari, Mohammad Ali (Business, Marketing, and Finance Open, 2026)
The continuation of economic sanctions and persistent financial difficulties for firms in recent years has highlighted the importance of managing cash flow volatility. In this context, based on stakeholder theory and legitimacy theory, the present study examines the effect of environmental information disclosure on cash flow volatility in order to better understand the determinants of reducing such volatility. Furthermore, to investigate heterogeneous effects arising from differences in firm characteristics, the moderating roles of firm size and ownership structure are also emphasized in this study. This research is a descriptive–correlational study conducted using a multivariate regression analysis approach. The screened statistical population consists of 153 companies listed on the Tehran Stock Exchange during the period from 2013 to 2022, yielding a total of 1,530 firm-year observations. The required data were collected from online information sources, including audited financial statements and annual performance reports available on the Codal system. Data analysis and hypothesis testing were performed using econometric techniques and EViews software. The findings indicate that environmental information disclosure leads to a reduction in cash flow volatility; however, this effect does not differ significantly between large and small firms, implying that firm size does not have a significant moderating effect on the relationship between environmental information disclosure and cash flow volatility. Nevertheless, the results reveal that the negative effect of environmental information disclosure on cash flow volatility is weakened in firms with government ownership structures.